The Influence of Market Orientation on Competitive Advantage and Business Performance - Muhammad Aufal Fresky Aufal; Zainul Arifin; Yusri Abdillah (Wacana: Jurnal Sosial dan Humaniora)
This research aims to examine the influence of Market Orientation (OP) and Competitive Advantage (CA) on Business Performance (BP) through Batik Micro and Small Enterprises in Klampar Village. This research aims to help Micro and Small Batik Enterprises in Klampar Village apply research results to improve market orientation excellence and competitive advantage in all market conditions. The research method used is quantitative. This research was conducted on Batik Micro and Small Businesses in Klampar Village, Pamekasan Regency, with a research sample of 60 Micro and Small Business Owners using non-probability sampling techniques with a census (saturated) sampling approach. Data were analyzed using PLS (Partial Least Square). The results showed that four hypotheses were rejected, three had a significant impact, and hypothesis one had an insignificant impact.: Market Orientation has a significant effect on Competitive Advantage, Market Orientation has an insignificant effect on Business Performance, Competitive Advantage has a significant effect on the Performance of Micro and Small Batik Businesses, and Market Orientation has an indirect impact on Business Performance through Competitive Advantage.